Isolation, identification and characterization of Jute Genomic LTR retrotransposon sequences - Siddiqi, Sadaf Saaz (BRAC University, 2012)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Masters of Science in Biotechnology, 2012